1987
DOI: 10.1111/j.1532-5415.1987.tb02313.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes in Postprandial Plasma Glucose, Insulin, and Free Fatty Acid Concentrations in Nondiabetic Individuals

Abstract: Plasma glucose, insulin, and free fatty acid (FFA) concentrations were measured from 0800 to 1600 hours in 40 nondiabetic individuals, separated into younger (38 +/- 1.4 years) and older (64 +/- 1.5 years) age groups. Meals were served at 0800 (20% total daily calories) and 1200 h (40% of total daily calories), and blood drawn just before the 0800 hours meal and at hourly intervals thereafter until 1600 hours. Statistical evaluation of the results of these measurements indicated that day-long plasma glucose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 16 publications
(16 reference statements)
3
26
0
Order By: Relevance
“…Aging is associated with alterations in body fat distribution, obesity and insulin resistance [113,114]. High levels of leptin are observed with obesity in humans and rodents [115,116].…”
Section: The Role Of Adipose Tissue In Aging Retardation By Dietary Rmentioning
confidence: 99%
“…Aging is associated with alterations in body fat distribution, obesity and insulin resistance [113,114]. High levels of leptin are observed with obesity in humans and rodents [115,116].…”
Section: The Role Of Adipose Tissue In Aging Retardation By Dietary Rmentioning
confidence: 99%
“…Aging is known to be associated with obesity phenotype, alterations in body fat distribution and the development of insulin and leptin resistance (Enzi et al, 1986;Fraze et al, 1987;Wang et al, 2001;Ma et al, 2002). Several reports have suggested that reduction in white adipose tissue (WAT) may be a primary factor in the longevity induced by CR.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of glycolysis was estimated from the rate of conversion of [ 3 H-3]glucose to 3 H 2 O as previously described (12,13). Because tritium on the C-3 position of glucose is lost to water during glycolysis, it can be assumed that plasma tritium is present either in 3 H water or in glucose. Plasma-tritiated water specific activity was determined by liquid scintillation counting of the protein-free supernatant (Somogyi filtrate) before and after evaporation to dryness.…”
mentioning
confidence: 99%